Paracetamol plus ibuprofen for the treatment of fever in children (PITCH): economic evaluation of a randomised controlled trial. (9th September 2008) - Hollinghurst, Sandra; Redmond, Niamh; Costelloe, Céire; Montgomery, Alan; Fletcher, Margaret; Peters, Tim J; Hay, Alastair D
Abstract : Objective To estimate the cost to the NHS and to parents and carers of treating febrile preschool children with paracetamol, ibuprofen, or both, and to compare these costs with the benefits of each treatment regimen. Design Cost consequences analysis and cost effectiveness analysis conducted as part of a three arm, randomised controlled trial. Participants Children between the ages of 6 months and 6 years recruited from primary care and the community with axillary temperatures ≥37.8°C and ≤41°C. Interventions Paracetamol, ibuprofen, or both drugs. Main outcome measures Costs to the NHS and to parents and carers. Cost consequences analysis at 48 hours and 5 days comparing cost with children's temperature, discomfort, activity, appetite, and sleep; cost effectiveness analysis at 48 hours comparing cost with percentage of children "recovered." Results Difficulties in recruiting children to the trial lowered the precision of the estimates of cost and some outcomes. At 48 hours, cost to the NHS was £11.33 for paracetamol, £8.49 for ibuprofen, and £8.16 for both drugs. By day 5 these costs rose to £19.63, £18.36, and £13.92 respectively. For parents and carers, the 48 hour costs were £23.86 for paracetamol, £20.60 for ibuprofen, and £25.07 for both, and the day 5 costs were £26.35, £29.90, and £24.02 respectively. Outcomes measured at 48 hours and 5 days were inconclusive because of lack of power; the cost effectiveness analysis at 48 hours provided little evidence that one treatment choice was significantly more cost effective than another. At 4 hours ibuprofen and the combined treatment were superior to paracetamol in terms of the trial primary outcome of time without fever; at 24 hours the combined treatment performed best on this outcome. Conclusions There is no strong evidence of a difference in cost between the treatments, but clinical and cost data together indicate that using both drugs together may be most cost effective over the course of the illness. This treatment option performs best and is no more expensive because of less use of healthcare resources, resulting in lower costs to the NHS and to parents.